2007
DOI: 10.1016/j.jacc.2006.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Long QT Syndrome in Adults

Abstract: The severity of LQTS in adulthood can be risk stratified with information regarding genotype, gender, QTc duration, and history of cardiac events. Beta-blockers effectively reduce but do not eliminate the risk of both syncopal and life-threatening cardiac events in adult patients with mutation-confirmed LQTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
233
2
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(266 citation statements)
references
References 23 publications
(23 reference statements)
10
233
2
12
Order By: Relevance
“…At adult age, LQT1 and LQT2 women have longer QT intervals and a higher risk of life-threatening cardiac events than men. 13,14 By contrast, before puberty, the incidence of arrhythmia is higher and occurred at a younger age in boys than in girls, 15 but the numbers of sudden deaths are similar between men and women LQTS patients in most of the studies, as it was in our cohort, where even more females than males died from non-arrythmogenic causes. Over several decades, β-blocker therapy has been used to prevent sudden death in LQTS patients, and intrauterine or infancy deaths due to LQTS remained exceptional.…”
Section: Discussionmentioning
confidence: 47%
“…At adult age, LQT1 and LQT2 women have longer QT intervals and a higher risk of life-threatening cardiac events than men. 13,14 By contrast, before puberty, the incidence of arrhythmia is higher and occurred at a younger age in boys than in girls, 15 but the numbers of sudden deaths are similar between men and women LQTS patients in most of the studies, as it was in our cohort, where even more females than males died from non-arrythmogenic causes. Over several decades, β-blocker therapy has been used to prevent sudden death in LQTS patients, and intrauterine or infancy deaths due to LQTS remained exceptional.…”
Section: Discussionmentioning
confidence: 47%
“…24,29,30 Data from the International Long QT Syndrome Registry indicate that among 1,496 enrolled subjects, the hazard ratio for cardiac events (arrhythmic syncope or probably long QT related death) is 1.052 x , where x is the per 10 msec unit increase in QTc. 24 A subject with a QTc of 450 msec therefore would have a 1.29-fold greater risk of a cardiac event than a subject with a QTc of 400 msec (1.052 5 ¼ 1.29).…”
Section: Discussionmentioning
confidence: 99%
“…One of the risk factors associated with sudden cardiac arrest in those with LQTS is a more prolonged QTc interval [55]. Those at greatest risk for SCD include individuals with a QTc interval >550msec [56]. Studies have shown that among 18 year olds with a QTc >550msec, 20% will experience SCA by age 40 [56].…”
Section: Non-structural Arrhythmia Related Causes Of Pediatric Suddementioning
confidence: 99%